The Rapes in Haiti: Psychological and Sociological Aspects of Sexual Crimes - Obrillant Damus (Études Caribéennes)
Rape is an event that induces an existential crisis by exerting a major impact on living for oneself, living together and living connected. It causes psychological and physical sufferings. Even after many years, most raped women have a traumatic memory of the event. The consequences of rape on the alteration of female identity are indisputable. The purpose of this article is to study the consequences of rape on the identity of victims; describe the feelings developed by the victims during and after the rape; understand how a victim manages to overcome the trauma of rape.